2012
DOI: 10.5851/kosfa.2012.32.5.591
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Meat Quality Traits, Free Amino Acid and Fatty Acid on Longissimus Lumborum Muscles from Hanwoo, Holstein and Angus Steers, Fattened in Korea

Abstract: This study was conducted to compare meat quality traits related to the tenderness of longissimus muscles obtained from domestic and imported steers. A total of 12 steers from three breeds were slaughtered, and were graded as quality grade 2. They were composed of 4 Hanwoo and 4 Holstein steers (domestic) as well as 4 Angus steers (imported from Australia and gained for six months in Korea until slaughtered). The longissimus lumborum muscles were separated and were stored at 4 o C for 7 and 14 d. Sarcomere leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…However, we also found significant differences between the monitored breeds in the musculus longissimus. Jeong et al (2012) focused on the comparison of meat quality traits, free amino acids, and fatty acids in longissimus lumborum muscles from Hanwoo, Holstein, and Angus steers, fattened in Korea. The results of this study have shown that there were no dramatic differences between beef from the three breeds that were fattened for 6 months under equal conditions.…”
Section: Resultsmentioning
confidence: 99%
“…However, we also found significant differences between the monitored breeds in the musculus longissimus. Jeong et al (2012) focused on the comparison of meat quality traits, free amino acids, and fatty acids in longissimus lumborum muscles from Hanwoo, Holstein, and Angus steers, fattened in Korea. The results of this study have shown that there were no dramatic differences between beef from the three breeds that were fattened for 6 months under equal conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the daily feed cost, feeding TMR in order to achieve Korean beef carcass standard (highly marbled beef) was not efficient in current study. Jeong et al (2012) found no differences in meat quality between Korean native cattle (Hanwoo) and Holstein steers that were finished under similar conditions on a high-energy diet for 6 months. However, the nutrient composition and daily intake of the conventional diet (TMR) used in this study differed from those of the diets that are commonly used for Hanwoo fattening programs in Korea (Panjono et al, 2009).…”
Section: Discussionmentioning
confidence: 81%
“…Cho et al [24] also reported lower C18:2 and PUFA percentages for the longissimus muscle fat of KC versus AN. In addition, Jeong et al [31] reported that the longissimus lumborum of KC had lower C18:2 and PUFA percentages than that of HO. Hwang and Joo [8] reported that C18:1n9 was positively associated with beef flavor, whereas PUFAs were negatively associated with beef flavor.…”
Section: Resultsmentioning
confidence: 99%